COMMENTED WRITTEN ERASURE: METALINGUISTIC ACTIVITIES PERFORMED DURING THE SCHOOL MANUSCRIPT UNDER CONSTRUCTION - Vanderlei, Kariny Amorim (2021)
This study aims to identify the metalinguistic activities carried out by two newly literate Portuguese students (aged 7 to 8 years) who collaboratively write the same text in the classroom. Two categories of analysis stand out: a) the occurrences of written erasures that appeared in the manuscript; b) comments regarding these erasures. Considered as reflection and metalinguistic activity, these erasures indicate the strong recursive character of the writing and the relationship of the writer with his text. The research data were collected in a basic education school in the city of Aveiro, in Portugal, through the methodological support offered by the Ramos System, a multimodal capture tool of the writing process. The results showed that the metalinguistic activities verbalized through the students' comments appear at different levels, both with the mention of appropriate linguistic terms and with the omission of these terms. In addition, there was a disagreement between its use and its function in the text.